ESG RATING DAN KINERJA PERUSAHAAN - Dhini Azhari; Erna Widiastuty (Universitas Muhammadiyah Bengkulu, 2025)
This study aims to examine the influence of Environmental, Social, and Governance (ESG) ratings on company performance in Indonesia. The research method used is a quantitative approach with panel data regression analysis on companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. The research sample consists of 45 companies with a total of 225 company-year observations selected using a purposive sampling method, with ESG ratings sourced from Refinitiv Eikon. Company performance is measured using Return on Assets (ROA) as a proxy for financial performance and Tobin's Q as a proxy for market performance, with firm size as a control variable. The results show that ESG ratings have a positive and significant effect on company financial performance (ROA), but a negative and significant effect on market performance as measured by Tobin's Q. Additional testing shows that the Environmental and Social components have a positive effect on ROA, while the Governance component shows no significant effect, and all ESG pillars have not significantly influenced market performance individually. The conclusion of this study shows that ESG ratings play a greater role in improving a company's internal performance than in shaping market value perceptions. Therefore, it is necessary to increase investor literacy and appreciation of sustainability practices so that ESG benefits can be more optimally reflected in the market valuation of companies in Indonesia. Keywords: SG Rating, Company Performance, Return On Assets, Tobin's Q, Sustainability